Biowaste utilization in the process of co-gasification with bituminous coal and lignite. (1st January 2017) - Howaniec, Natalia; Smoliński, Adam
Abstract: Biowaste utilization in co-gasification with bituminous coal and lignite gives the benefits of stable supplies of a primary energy source – coal and utilization of a zero-emission, waste material (i.e. agriculture waste, sewage sludge, etc.) with higher process efficiency and lower negative environmental impact than biomass or coal gasification, respectively. The main focus of the study presented is co-gasification of bituminous coal or lignite with biowaste to hydrogen-rich gas. The experiments were performed in the laboratory scale fixed-bed reactor installation at 700 and 900 °C. The Hierarchical Clustering Analysis complemented with a color map of studied data were applied in the selection of the optimal operating parameters for biowaste utilization in the co-gasification process based on the experimental data of gasification/co-gasification process as well as physical and chemical properties of fuels tested. The experimental results showed that the carbon conversion rate in co-gasification increased with increasing biomass content in a fuel. The total gas volume and hydrogen volume in co-gasification were higher than the values expected based on the results of the gasification process of the fuels analyzed. Highlights: Biowaste co-gasification with bituminous coal/lignite to hydrogen-rich gas. Steam co-gasification in laboratory scale fixed-bed reactor at 700 and 900 °C. Hierarchical Clustering Analysis complemented with color map of experimental data. Carbon conversion increase with increasing biomass content. The highest total gas and hydrogen volume in co-gasification of C-B20 blend at 900C.